4D printing for modular construction components – Applications and main developments - Renata Morbiducci; Salvatore Polverino; Caterina Battaglia (Agathón)
Since the end of the 20th century, a rapid expansion has characterised digital fabrication techniques in different areas of human activity. In particular, in the construction sector, their use has enabled the production of unprecedented modular components that can be customised according to specific application requirements. This includes the use of additive manufacturing techniques employing 4D printing for the production of responsive modular elements. However, despite being able to contribute to mitigating the effects of climate change, they are still scarcely used. This essay intends to analyse the main peculiarities of 4D printing techniques for the production of modular elements for architecture, highlighting their main limitations and potentialities that influence their use.